Protection of copper corrosion in acidic medium using pinostrobin - Rosita Wati; Saprizal Hadisaputra; Dina Asnawati; Dhony Hermanto (Acta Chimica Asiana, 2018)
The corrosion inhibition efficiency of copper was tested by the weight loss method in 1 M H2SO4 medium in the presence of pinostrobin as inhibitor. It shows that the addition of pinostrobin inhibitor reduce the corrosion rate. The nature of thermodynamic of pinostrobin adsorption on copper surfaces follows the Freundlich isotherm. The process of inhibition is endothermic, spontaneous and physisorption. It is proved by the Ea, Î”H and Î”S and Î”G values in which the thermodynamic studies show that the values of Ea < 80 kJ.mol-1, âˆ†H positive, âˆ†S positive, and Î”G < -20 kJ.mol-1.